Awareness of Physicians in Yemen Toward High Blood Pressure Management According to the Eighth Joint National Committee (JNC 8) Guideline - Halboup, Abdulsalam M.; Othman, Gamil Q.; Battah, Mohammed M.; Alzoubi, Karem H.; Sallom, Hebah (Dove Medical Press, 2020)
Background: Hypertension is a common public health problem that impacts more than one-third of the world population. Awareness of physicians towards the guidelines of high blood pressure management is an essential step to reduce the consequences of high blood pressure. Objective: This study was aimed to assess the awareness of physicians towards high blood pressure treatment according to the recent report of the Joint National Committee (JNC8) guideline. Methods: A self-administered questionnaire was distributed to 400 physicians during the period from February to April 2017. Physicians were recruited from public and private hospitals as well as clinics. A validated questionnaire that incorporated the changes seen in JNC 8, as well as the specific modality of hypertension management based on other guidelines, was administered to the participating physicians. Results: Three hundred and eighty-nine physicians completed the questionnaire; with all the interviewed physicians have ever heard about JNC 8. The practice of general practitioners (GPs) was significantly deviated from the recommended guideline of blood pressure management as compared to consultants, specialists, and residents. Additionally, certain variations were found among consultants, specialists, and residents with slight superiority of consultants towards most aspects. Conclusion: The finding of this study highlights an inadequate knowledge of GPs in Yemen towards high blood pressure management guidelines. The findings of this study emphasize the necessity for continuous medical education programs that are specially designed to target GPs. Continued update of medical curricula in Yemeni universities is also needed.